Kekuatan Hukum dan Aspek Keamanan Dalam Tanda Tangan Elektronik - Triana Wati (JOURNAL SAINS STUDENT RESEARCH, 2023)
An Electronic Signature is an electronically generated signature used for authentication and verification of electronic documents. Electronic Signature has the potential to replace wet signatures in a variety of transactions, including contracts, agreements, and other legal documents. Electronic Signature is regulated in Law Number 11 of 2008 concerning Electronic Information and Transactions. Article 11 of the Electronic Signature Law states that Electronic Signature has legal force and legal consequences that are valid and binding as long as it meets certain requirements. The security aspect is also an important consideration in the use of Electronic Signature. Electronic Signature must be guaranteed authenticity and integrity so that it cannot be falsified or altered. This journal discusses the legal strength and security aspects of Electronic Signature. This journal aims to provide a better understanding of Electronic Signature and how Electronic Signature can be used safely and effectively in various transactions